1996
DOI: 10.1063/1.361484
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water and alcohols on photoluminescence of porous silicon

Abstract: The measurements of luminescence spectra were performed on series of porous silicon (PS) samples, obtained in wide range of anodic etching regimes. Photoluminescence (PL) spectra contain two closely spaced luminescence bands. The energy difference between them ∼0.15–0.2 eV depends very slightly on their spectral position. The ratio of the intensities of the two PL bands is monotonously changing with the changes in sample porosity. Thus, in very porous samples only the short-wavelength band is usually observed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Earlier defect-related luminescent materials were mainly based upon silica and silica-based materials, including silicatecarboxylate, 17 SiO 2 glass, 18,22 SiO 2 gels, 27,28 SiO 2 spheres, 111,114 organic/inorganic hybrid silicones, [23][24][25] silica nanotubes, 148 molecular sieves, 31,149 etc. [150][151][152][153][154][155][156] As the most promising materials for environmentally friendly phosphors, these kinds of luminescent materials have been the focus of research efforts since the pioneering work of Sailor and co-workers. 17,121 It has been reported that a kind of white phosphor with high emissive broadband spectra (Fig.…”
Section: Silica and Silica-based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier defect-related luminescent materials were mainly based upon silica and silica-based materials, including silicatecarboxylate, 17 SiO 2 glass, 18,22 SiO 2 gels, 27,28 SiO 2 spheres, 111,114 organic/inorganic hybrid silicones, [23][24][25] silica nanotubes, 148 molecular sieves, 31,149 etc. [150][151][152][153][154][155][156] As the most promising materials for environmentally friendly phosphors, these kinds of luminescent materials have been the focus of research efforts since the pioneering work of Sailor and co-workers. 17,121 It has been reported that a kind of white phosphor with high emissive broadband spectra (Fig.…”
Section: Silica and Silica-based Materialsmentioning
confidence: 99%
“…Apart from this, silica gels have been also extensively investigated as defect-related phosphors. Among them, silica aerogels, which are well-known to show photoluminescence generally from the blue to red spectral regions, exhibited several structural defects advantageous to photoluminescent properties, such as a nonbridged oxygen hole center (NBOHC) (described as SiOH -SiO + H; this defect was connected with bands at 1.8 and 1.9 eV), [151][152][153] peroxy linkage (POL) (labeled as ROO , where R represents an unspecified radical or part of the structure), 154 and E 0 center (RSi ) on the basis of the basic emission characteristic band at 2.2 eV in the PL spectra. 152,156 In addition, Hinic´'s group has reported PL spectra measured for two series of silica aerogel sintered at 1000 1C for different time intervals.…”
Section: Silica and Silica-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant challenge associated with elemental Si-NCs is the propensity to oxidize in the presence of air and water. 50 Oxidation diminishes the reactive hydride surface, destroys the crystallinity and can influence photoluminescence intensity. However, oxidation can be minimized by covalent functionalization of ligands to the surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 It is known that porous silicon matter possesses unique photoluminescence when excited by ultraviolet light. 23,24 The current nanofibrous silicon sheet derived from filter paper is obviously porous with high specific surface areas replicated from the initial cellulose structures. It showed strong blue photo-luminescence under ultraviolet light (Fig.…”
Section: Photo-luminescent Properties Of the Silicon Replicasmentioning
confidence: 99%